Response of Growth and Yield of "IPB 9G" Rice to The Application of NPK and Biofertilizers - Manullang, Frisca Anggriani; Lubis, Iskandar; Munif Ghulamahdi (Journal of Tropical Crop Science, 2025)
Rice is a staple food crop that is challenging to replace with alternative crops. Strategies that balance high yields with environmental sustainability are crucial to enhance rice production. One such approach is integrating organic, biological, and chemical fertilizers. This study aimed to evaluate the effects of combining these fertilizers on the growth and yield of "IPB 9G" rice. The experiment was conducted at the IPB experimental farm in Cikabayan, Bogor, Indonesia, from March to June 2024, using a randomized complete block design with two factors and three replications. Treatments included two doses of NPK fertilizer (100% and 50% of the recommended dose) and five combinations of organic and biofertilizers: Azotobacter sp., Azotobacter sp. + Pseudomonas sp., humic acid, PGPR (Plant Growth-Promoting Rhizobacteria), and a combination of Azotobacter sp. + Pseudomonas sp. + humic acid + PGPR. Parameters observed included leaf area, root volume, shoot dry weight, and yield components such as the number of panicles, 1000-grain weight, and the number of grains per panicle. The results demonstrated a significant interaction between NPK dosage and organic-biofertilizer combinations on plant growth and yield. Notably, applying 50% of the recommended NPK dose combined with Azotobacter sp. + Pseudomonas sp. produced comparable or superior yields to the full NPK dose. These findings highlight the potential of reducing chemical fertilizer usage by incorporating biofertilizers, offering an environmentally sustainable strategy for rice cultivation.